The Effects of Managerial Ownership on Real Earnings Management and Company’s Performance in Malaysia - Mohd Taufik MOHD SUFFIAN; Rahayu ABDUL RAHMAN; Zuraidah MOHD SANUSI; Naimah AHMAD YAHYA (Communications of International Proceedings, 2020)
This study examines the effects of managerial ownership on real earnings management and company’s performance in Malaysia. By utilising the data from 646 Bursa Malaysia-listed companies that were active from 2013 until 2017, the panel results show that managerial ownership have negatively significant relationship with real earnings management proxy by abnormal cost of goods sold and negatively significant with company’s performance proxy by Tobin’s Q. This result aligned the Agency Theory that concerns the problems between managers and shareholders. The result also depicts that the earnings management is strongly related to the performance of the company. It is an essential resource for any market participant since it provides a reduced volume of information asymmetries between managers, investors, regulatory agencies, society and other stakeholders. The current findings can be treated as tools to lessen the earnings management activities and to increase the company’s performance by the management and stakeholders by applying monitoring mechanisms on companies through managerial ownership which have to curtail opportunistic behaviour among the management.
Keywords: Managerial Ownership; Earnings Management; Company’s Performance.